Effect of Authentic Leadership on Employees’ Engagement and Job Satisfaction: A Case Study of Public Sector Universities - Adil, Hejratullah; Tariq, Ahmad; Shinwari, Aminullah; Sabah, Sabahuddin (Eximia, 2023)
Several studies have suggested that leaders showing high levels of authentic leadership increase workers’ engagement and job satisfaction. The study was conducted to examine the effect of authentic leadership on employees’ engagement and job satisfaction. The study focused in the public sector universities operating in Eastern Zone. The faculty members working at Nangarhar University, Laghman University, Sayed Jamaluddin Afghan University and Nuristan Institute of Higher Education was taken as the target population of the study. From these employees, 143 were selected as a sample of the study using proportional allocation method. Descriptive, regression techniques and reliability statistics were used to analyze the data. As per the results of reliability statistics, scales for authentic leadership (.827), employees’ engagement (.924) and job satisfaction (.744) were found highly reliable. According to regression results of testing hypotheses, the result of authentic leadership has positive significant effects on employee engagement and on job satisfaction. This research will help academic professionals in public sector universities to know how authentic leadership style influences positively employees’ engagement and job satisfaction.